2001
DOI: 10.1073/pnas.231484998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of five new genes on the Y chromosome of Drosophila melanogaster

Abstract: The heterochromatic state of the Drosophila Y chromosome has made the cloning and identification of Y-linked genes a challenging process. Here, we report application of a procedure to identify Y-linked gene fragments from the unmapped residue of the whole genome sequencing effort. Previously identified Y-linked genes appear in sequenced scaffolds as individual exons, apparently because many introns have become heterochromatic, growing to enormous size and becoming virtually unclonable. A TBLASTN search using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
183
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 38 publications
9
183
0
2
Order By: Relevance
“…The Y chromosome is required for male fertility in most Drosophila species (Ashburner et al, 2005) even though it does not contain a male-determining gene. Instead, most if not all of the~14 protein-coding genes present on the Y chromosomes of Drosophila melanogaster, D. simulans and other closely related species have male-specific functions and are exclusively expressed in the testis (Gepner and Hays, 1993;Carvalho et al, 2000;Carvalho et al, 2001;Vibranovski et al, 2008). Nevertheless, a suite of studies have shown that genetic variation present on the Y of Drosophila underlie phenotypic variation in male fitness (Chippindale and Rice, 2001;Yee et al, 2015), sex ratio distortion (Carvalho et al, 1997;Montchamp-Moreau et al, 2001;Branco et al, 2013a, b), tolerance to temperature extremes (Rohmer et al, 2004;David et al, 2005), behavior (Stoltenberg and Hirsch, 1997;Huttunen and Aspi, 2003), gene expression (Lemos et al, 2008;Sackton et al, 2011;Branco et al, 2013a, b) and chromatin states in somatic tissues .…”
Section: Introductionmentioning
confidence: 99%
“…The Y chromosome is required for male fertility in most Drosophila species (Ashburner et al, 2005) even though it does not contain a male-determining gene. Instead, most if not all of the~14 protein-coding genes present on the Y chromosomes of Drosophila melanogaster, D. simulans and other closely related species have male-specific functions and are exclusively expressed in the testis (Gepner and Hays, 1993;Carvalho et al, 2000;Carvalho et al, 2001;Vibranovski et al, 2008). Nevertheless, a suite of studies have shown that genetic variation present on the Y of Drosophila underlie phenotypic variation in male fitness (Chippindale and Rice, 2001;Yee et al, 2015), sex ratio distortion (Carvalho et al, 1997;Montchamp-Moreau et al, 2001;Branco et al, 2013a, b), tolerance to temperature extremes (Rohmer et al, 2004;David et al, 2005), behavior (Stoltenberg and Hirsch, 1997;Huttunen and Aspi, 2003), gene expression (Lemos et al, 2008;Sackton et al, 2011;Branco et al, 2013a, b) and chromatin states in somatic tissues .…”
Section: Introductionmentioning
confidence: 99%
“…(51) A new computational analysis of the D. melanogaster genome may shed light on this matter, however, it complements the data on transposition of autosomal genes into the Y chromosome. (8) Computational approaches to reveal Y chromosome genes and their autosomal counterparts Carvalho and colleagues developed a computational method to identify the genes essential for male fertility on the Drosophila Y chromosome. (8) This method involves revealing the homologs of protein-coding DNA sequences among nonrepetitive unmapped sequences in D. melanogaster.…”
Section: Accumulation Of Transposable Elements On the Y Chromosomementioning
confidence: 99%
“…(8) Computational approaches to reveal Y chromosome genes and their autosomal counterparts Carvalho and colleagues developed a computational method to identify the genes essential for male fertility on the Drosophila Y chromosome. (8) This method involves revealing the homologs of protein-coding DNA sequences among nonrepetitive unmapped sequences in D. melanogaster. They found Y-linked coding sequences with large introns containing repetitive sequences.…”
Section: Accumulation Of Transposable Elements On the Y Chromosomementioning
confidence: 99%
See 2 more Smart Citations